Evaluation of the Potential of Jack Bean [Canavalia Ensiformis (L.) Dc.] and Velvet Bean [Mucuna Pruriens (L.) Dc.] Aqueous Extracts as Post-Emergence Bio-Herbicides for Weed Control in Maize (Zea Mays L.) - J. T , Rugare; P. J , Pieterse; S, Mabasa (Asian Journal of Agriculture and Rural Development, 2020)
The objective of the study was to evaluate the effect of jack bean and velvet bean aqueous extracts when applied post-emergence alone or in combination with half dosage rates of atrazine on goosegrass, beggarticks, and maize. Three potted experiments with fifteen treatments were laid out in a completely randomized design replicated four times and repeated once. The bio-herbicidal treatments were applied to maize at two weeks after crop emergence and on the weeds at the 3-4 leaf stage. Results showed that maize height increased significantly (p<0.05) across all treatments from 24 to 34 days after crop emergence (DACE). Maize chlorophyll content significantly (p<0.05) increased from 24 to 34 DACE in all the treatments. In contrast, dry weight, height, and chlorophyll content of goosegrass were significantly (p<0.05) reduced by all treatments. The height of beggarticks was not significantly (p>0.05) affected while chlorophyll content and dry weight were significantly (p<0.05) reduced by all treatments. All the treatments caused complete weed control at 6 and 10 DAS in beggarticks and goosegrass, respectively. It was concluded that velvet bean and jack bean aqueous extracts are phytotoxic to weeds of divergent morphology.